2012
DOI: 10.1088/2040-8978/14/7/075101
|View full text |Cite
|
Sign up to set email alerts
|

High negative refractive index in chiral metamaterials

Abstract: Conjugated bi-layer C8 metamaterials are proposed. Chirality and refractive index can be controlled effectively by the structure geometry. Extreme chirality results in a high negative refractive index for both right- and left-circular polarized excitations. The conjugated bi-layer C8 structures are fabricated and tested in microwave regimes. The measurement results are in good agreement with the simulation results. These proposed structures are additional promising candidates for high negative refractive index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Generally, we can use the effective loss factor characterize how well the MMs behaves. The effective loss factor can be expressed as LF = |Im(n)/Re(n)| for average refractive index, and the loss factor of RCP and LCP can be expressed as LF = |Im(n ± )/Re(n ± )| [23,24]. The LF of the effective refractive index is less than 0.2 at resonances, which indicated that the loss of the proposed dual-band CMMs is relative small.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Generally, we can use the effective loss factor characterize how well the MMs behaves. The effective loss factor can be expressed as LF = |Im(n)/Re(n)| for average refractive index, and the loss factor of RCP and LCP can be expressed as LF = |Im(n ± )/Re(n ± )| [23,24]. The LF of the effective refractive index is less than 0.2 at resonances, which indicated that the loss of the proposed dual-band CMMs is relative small.…”
Section: Resultsmentioning
confidence: 96%
“…3(a), similar to the previous designed novel dual-band structure [20], the real part of chiral parameter Re(κ) .1) at these resonant frequencies, which indicate that the proposed MMs can achieve dualband negative refractive properties in THz region. The generations of the negative refractive indices are mainly due to the high chirality of the designed structure [3,24]. Generally, we can use the effective loss factor characterize how well the MMs behaves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability is called as optical activity attracting many scientists for its potential application areas in scientific world, for example, analytical chemistry, molecular biology etc. Chiral media belong to a wider range of bi-isotropic media and it is characterized by [1][2][3][4] …”
Section: Introductionmentioning
confidence: 99%
“…Chiral MTMs have received considerable attention in recent years for their ability to exhibit unusual electromagnetic (EM) properties such as strong optical activity [1], circular dichroism [2] and negative refraction [3], which are not seen in conventional materials. They are characterized by the quantity of chirality parameter, = ( − ) 2 ⁄ , where ⁄ is ratio representing the refractive indexes of the right circularly polarized (RCP) and left circularly polarized (LCP) waves and high chirality values lead to negative refractive index [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%